Gaian Systems : Lynn Margulis, Neocybernetics, and the End of the Anthropocene - Clarke, Bruce, 1950- (Book collections on Project MUSE., 2020)
"A groundbreaking look at Gaia theory's intersections with neocybernetic systems theory"--